Health Literacy on Eating, Exercise, Emotion Health Behaviors Among Nursing Students - Phongsakchat, Payao; Areesophonpichet , Sornnate; Navicharern, Rungrawee (Dusit Thani College Journal, 2020)
The purposes of this research were to study the health literacy on 3E (Eating - Exercise - Emotion) health behaviors among nursing students in Praboromarajchanok Institute, Ministry of Public Health and compare their health literacy regarding their levels of class and regions. The sample size was 390 nursing students studying in the first to fourth years during academic year 2017 from 12 nursing colleges located in the north, central, south, and northeast part of Thailand. The questionnaire was the health literacy questionnaire of nursing students and the Cronbach’s alpha coefficient was 0.92. The results showed that nursing students from nursing colleges located in the north part of Thailand had the highest health literacy average scores, and the lower average scores were those in the south, northeast, and central regions respectively. The 3rd year nursing students had the highest health literacy average scores, and the lower average scores were those in the 4th, 2nd, and 1st years respectively. The average scores of the health literacy regarding the understanding of health information and applying health information to make decision on health promotion were higher than those regarding the access to health information and the appraisal of the value of health information. In addition, the average scores of health literacy among the levels of class, and regions of the sample were statistically significant difference F(3, 386) = 3.46, p=0.02 and F(3, 386) = 3.02, p=0.03) respectively.